Wound prevalence survey in a regional integrated care organisation in the midwest of Ireland. (2nd June 2021) - Meagher, Helen; Keane, Niamh; Egan, Siobhan; Sheikhi, Ali; Moloney, Michael A.; Kavanagh, Eamon
Abstract : Background/aims: The aim of this clinical audit was to determine the point prevalence of wounds over a 1-week period during April 2019 in the midwest Regional Integrated Care Organisation (RICO), which has a population of 379 452. The RICO consists of six hospitals, a public health nursing service across three counties, community residential settings, nine older person's service sites, community health centres and one prison. Method: A peer-reviewed, purpose-designed data collection tool was used to gather demographic and wound data on each patient with a wound in the midwest RICO. Anonymised data were collected by the nurse undertaking routine wound care on one occasion during the 1-week study period. There were no exclusion criteria for this study; all patients with a wound were eligible for inclusion. Ethical approval was obtained. Results: Completed data collection forms were returned for 791 patients who had a combined total of 1164 wounds. Data were analysed using SPSS version 21 to produce descriptive statistics. A point prevalence of 0.2% of the total RICO population had a wound, with a mean of 1.47 wounds per patient. Some 51% of the cohort was female. The median age was 75 years (range 3–101 years, standard deviation=19.881). Leg ulcers were the most common wound type, with a prevalence of 0.07% (33.7% of the cohort). Conclusions: This clinical wound prevalence audit supports previous studies in relation to wound statistics in Ireland and will be useful for resource planning in an ageing population.